Assessing a Human Rights-Based Approach to HIV Testing and Partner Notification in Kenya: A Qualitative Study to Examine How Kenya's Policies and Practices Implement a Rights-Based Approach to Health - Neiloy R. Sircar; Allan A. Maleche (Harvard FXB Center for Health and Human Rights, 2020)
Kenya encourages HIV testing and notification services, especially for key and affected populations (KAP), in order to identify persons living with HIV and link them to treatment. Kenya and international supporters of its HIV program have sought to scale up these services through increased capacity and training. However, little is known about how the HIV strategy is implemented and sustained, particularly regarding human rights. Kenya aspires to support human rights in adherence to a human rights-based approach (HRBA) to HIV. This exploratory qualitative study assesses Kenya's progress in implementing an HRBA to HIV. KAP participants conveyed mixed perspectives on their HIV care services, conveying distrust in Kenya's public health care system while also recognizing improvement in some patient-provider interactions. Providers see the need to better engage KAP through community-based organizations and undergo improved, consistent training to sustain practices and policies that promote their rights realization. We believe that our study contributes to both HIV and human rights research by capturing successes and challenges in Kenya's implementation of an HRBA to HIV. These findings should inform future collaboration between Kenyan health authorities and KAP, and shape HIV policies and practices to improve health care utilization and human rights realization.